Genome-Based Metabolic Reconstruction of a Novel Uncultivated Freshwater Magnetotactic coccus “Ca. Magnetaquicoccus inordinatus” UR-1, and Proposal of a Candidate Family “Ca. Magnetaquicoccaceae” - Koziaeva, Veronika; Dziuba, Marina; Leão, Pedro; Uzun, Maria; Krutkina, Maria; Grouzdev, Denis (Frontiers in Microbiology, 2019)
Magnetotactic bacteria are widely represented microorganisms that have the ability to synthesize magnetosomes. The magnetotactic cocci of the order Magnetococcales are the most frequently identified, but their classification remains unclear due to the low number of cultivated representatives. This paper reports the analysis of an uncultivated magnetotactic coccus UR-1 collected from the Uda River (in eastern Siberia). Genome analyses of this bacterium and comparison to the available Magnetococcales genomes identified a novel species called ‘Ca. Magnetaquicoccus inordinatus’, and a delineated candidate family ‘Ca. Magnetaquicoccaceae’ within the order Magnetococcales is proposed. We used average amino acid identity values <55–56% and <64–65% as thresholds for the separation of families and genera, respectively, within the order Magnetococcales. Analyses of the genome sequence of UR-1 revealed a potential ability for a chemolithoautotrophic lifestyle, with the oxidation of a reduced sulfur compound and carbon assimilation by rTCA. A nearly complete magnetosome genome island, containing a set of mam and mms genes, was also identified. Further comparative analyses of the magnetosome genes showed vertical inheritance as well as horizontal gene transfer as the evolutionary drivers of magnetosome biomineralization genes in strains of the order Magnetococcales.